Vitamin B and Vitamin C Affect DNA Methylation and Amino Acid Metabolism in Mycobacterium bovis BCG - Song, Ningning; Zhu, Yongqiang; Cui, Yingying; Lv, Mingyue; Tang, Yiyi; Cui, Ziyin; Dang, Guanghui; Zheng, Huajun; Liu, Siguo (Frontiers in Microbiology, 2020)
Vitamins are essential nutrients and key cofactors of enzymes that regulate cellular metabolism, and also activate the immune system. Recent studies have shown that vitamin B1 (VB1) and vitamin C (Vc) can inhibit Mycobacterium tuberculosis growth, but the precise mechanism is still not well understood. In the present study, we have used RNA-sequencing (RNA-seq), liquid chromatography coupled to mass spectrometry (LC-MS) and single-molecule real-time (SMRT) sequencing to analyze the transcriptional, metabolic and methylation profiles of Mycobacterium bovis BCG when treated with VB1 and Vc. Our results show that, after vitamin treatment, variant metabolites were mainly clustered in pathways related to amino acid metabolism. Treatment with both vitamins significantly up-regulated the gene encoding cysteine synthase A. Additionally, only BCG that was treated with VC showed m4c modifications. Genes harboring this methylation were up-regulated, suggesting that m4c methylation can promote gene transcription to some extent. Overall, this study contributes to the understanding of the effects of VB1 and VC, and suggests that these vitamins constitute potential anti-tuberculosis drugs.